Secukinumab is superior to fumaric acid esters in treating patients with moderate‐to‐severe plaque psoriasis who are naive to systemic treatments: results from the randomized controlled PRIME trial. (12th September 2017) - Sticherling, M.; Mrowietz, U.; Augustin, M.; Thaçi, D.; Melzer, N.; Hentschke, C.; Kneidl, J.; Sieder, C.; Reich, K.
Summary: Background: Secukinumab is a fully human antibody that neutralizes interleukin‐17A. It has significant efficacy and a favourable safety profile in moderate‐to‐severe plaque psoriasis and psoriatic arthritis. Objectives: To compare secukinumab with fumaric acid esters (FAEs) in a randomized controlled trial. Methods: In this 24‐week, randomized, open‐label, multicentre study with blinded assessment, patients with moderate‐to‐severe plaque psoriasis, naive to systemic treatments, were randomized to receive secukinumab 300 mg subcutaneously or oral FAEs. The primary end point was ≥ 75% improvement from baseline Psoriasis Area and Severity Index score (PASI 75 response) at week 24, and missing patients were considered responders if they were responders at the time of dropout. Results: In total 202 patients were randomized and 200 were treated with at least one dose. Outcomes at week 24 were available for 147 and imputed for 53 patients. Discontinuations were mostly due to adverse events, which occurred more frequently in the FAE group (1·9% vs. 33·0%). At week 24, significantly more patients receiving secukinumab compared with FAEs achieved PASI 75 response (89·5% vs. 33·7%, P < 0·001), PASI 90 response (81·0% vs. 28·4%, P < 0·001) and Dermatology Life Quality Index 0 or 1 response (71·4% vs. 25·3%, P < 0·001). Conclusions: Secukinumab demonstrated superior efficacy to FAEs in patients with psoriasis over a 24‐week period. Abstract : What's already known about this topic? In Europe, secukinumab was the first biological therapy to be approved as a first‐line treatment. Secukinumab demonstrated superiority to etanercept and ustekinumab in the clearing of skin symptoms, but has not yet been compared with first‐line systemic treatments. Fumaric acid esters (FAEs) are recommended as a first‐line treatment by the European S3‐Guidelines. What does this study add? This head‐to‐head study showed that secukinumab has significantly greater efficacy in patients with psoriasis in terms of achieving ≥ 75% improvement in Psoriasis Area and Severity Index (PASI 75) response at week 24. PASI 50, 90 and 100 responses were all higher for secukinumab vs. FAEs at week 24. Secukinumab showed a favourable safety profile, and fewer patients discontinued secukinumab due to adverse events compared with patients on FAEs. Linked Comment:Balak. Br J Dermatol 2017; 177:897–898 . Respond to this article